The impact of COVID-19 pandemic on sleep duration and mental health among middle school students: a 3-year cross-sectional survey - Dou, Kai-yun; Dong, Ru-bao; Gan, Chun-long (Frontiers in Public Health, 2025)
BackgroundSince the outbreak of COVID-19 in late 2019, and until the Chinese government downgraded the pandemic control measures to Category B management in January 2023, various epidemic prevention measures were implemented across regions based on the local spread of the virus. Correspondingly, educational formats shifted between online and offline teaching according to the pandemic situation. Changes in daily life and teaching methods, along with the high initial mortality rate of COVID-19, have had varying degrees of negative impact on the mental health (MH) of adolescents.PurposesThis study aimed to explore the impact of the COVID-19 pandemic status on the sleep duration (SD) and MH of adolescents, investigate the relationship between SD and MH in middle school students, and evaluate the protective effect of SD on MH.MethodsUsing a convenient sampling method, 6 junior high schools and 3 senior high schools in Guiyang City, China, were selected. Random samples from two classes per grade in each school were chosen for the survey. The study was conducted annually for three consecutive years using the Mental Health Inventory of Middle-school students (MMHI-60) scale and a self-designed questionnaire. Data were analyzed using IBM SPSS version 26.0 software, employing ANOVA, cross-tabulation, and generalized linear models to examine the relationship between SD and MH scores.ResultsThe SD and MH scores of middle school students in 2021, 2022, and 2023 were 436.41 ± 71.21 min/day, 423.69 ± 61.71 min/day, and 445.26 ± 65.04 min/day (F = 41.44, p < 0.001), 1.72 ± 0.63, 1.87 ± 0.73, and 1.79 ± 0.67 (F = 18.31, p < 0.001). The SD compliance rates were 34.1%, 23.9%, and 33.2%, and the MH problem detection rates were 27.9%, 36.4%, and 33.4%, respectively; there is a significant correlation between SD and MH scores among middle school students (P < 0.001); the protective effects of SD compliance on MH were 1.859 times, 2.156 times, and 1.516 times higher than those of SD non-compliance (all p < 0.001).ConclusionMeeting the SD standard is a protective factor for adolescent MH. The COVID-19 pandemic and its control measures have had a severe and long-term negative impact on both SD and MH in middle school students, with differences observed between genders and academic levels. The greater the severity of the pandemic and the stricter the control measures, the more significant the negative impact on SD and MH etc.